Caracterização antropométrica e desempenho motor de escolares praticantes de Jiu-jítsu - Silva, Allen Gabriel da Silva e (Brasil, 2025)
The present study aimed to characterize the anthropometric parameters and motor performance of schoolchildren practicing Jiu-Jitsu. The research, of a descriptive and exploratory nature, included a sample of 12 male students. Anthropometric measurements included height, wingspan, body weight, fat percentage, muscle mass percentage and body mass index (BMI), determined by bioimpedance. Motor performance was assessed using the sit-and-reach, modified sit-up, 4x4 square run, horizontal jump strength and hand grip tests. The results showed that the fat percentage was mostly classified as "very good" or "excellent", with only one participant being overweight. The balanced body composition was positively reflected in the strength, flexibility and agility tests, in which the practitioners performed above average, with ratings between "very good" and "excellent". Furthermore, minimal differences in strength were observed between the hands, indicating muscular balance. These findings highlight the benefits of systematic training in Jiu-Jitsu, with significant impacts on physical fitness, especially on flexibility, strength and muscular endurance. The study reinforces the relevance of Jiu-Jitsu as a sports modality for physical and motor development during childhood and adolescence, contributing to the prevention of problems related to a sedentary lifestyle, such as obesity and postural changes, and promoting motor skills that are fundamental to quality of life and sports performance.